Zebrafish embryos as in vivo test tubes to unravel cell-specific mechanisms of neurogenesis during neurodevelopment and in diseases. Issue 1 (1st January 2016) - Samarut, Éric
ABSTRACT: Zebrafish has become a model of choice for developmental studies in particular for studying neural development and related mechanisms involved in diseases. Indeed, zebrafish provides a fast, handy and accurate model to perform functional genomics on a gene or network of genes of interest. Recently, we successfully purified neural stem cells (NSCs) by fluorescence-activated cell sorting (FACS) from whole embryos in order to analyze cell-specific transcriptomic effects by RNA sequencing. As a result, our work sheds light on signaling pathways that are more likely to be involved in our morpholino-induced neurogenesis phenotype. This cell purification strategy brings zebrafish to a higher level since it now allows one to investigate cell-specific effects of a genetic condition of interest (knockout, knock-down, gain-of-function etc.) at the genomic, transcriptomic and proteomic levels in a genuine in vivo context. With this new potential, there is no doubt that zebrafish will be of a major model with which to unravel complex underlying molecular mechanisms of neurological disorders such as epilepsy, autism spectrum disorders and schizophrenia.